“Where the misery and disgraced state of country are hidden”: Antônio Muniz de Souza and the maxims for travelers in the Empire of Brazil (1843) (PerCursos, 2024)
Antônio Muniz de Souza (1782-1857) was a black letter born in ancient Brazil and who, throughout the first half of the 19th century, traveled through the backlands of the Empire. As a result of these experiences as traveler, in 1843 he published the book “Maxims and thoughts”, a work in which he presented some guidelines for the conduct of men who were interested in traveling around the country. Based on the mobilization of this historiographical source, this article has at its core understanding the conception of black letter regarding the role attributed to travelers in a country that was in the process of building its autonomy.
Keywords: Antônio Muniz de Souza; provinces in northen Brazil; travelers; XIX century; backlands